STRATEGY FOR ACCELERATING ECONOMIC RECOVERY COVID 19 PANDEMIC TIME IN THE CITY AND DISTRICT OF KEDIRI (REVIEW OF ECONOMIC GROWTH THEORY OF KARL BUCHER AND MAQASHID SYARIAH) - Andriani, Andriani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
The strategy for accelerating economic recovery after the pandemic is an important policy for each region. Through several programs that have been made to increase community economic growth due to the pandemic outbreak. The Government of Kediri City and Kediri Regency have several different programs in community economic recovery. According to Karl Bucher, economic growth goes through several stages. Whereas in Islam the policies made for the community must be in creating benefit. In addition, it is important to pay attention to the five aspects of Maqashid Sharia such as Ad-din, An-nas, Al-aql, An-nasl, and Almal. Therefore, this study will review the programs carried out by the government of Kediri City and Kediri Regency in economic recovery based on the economic growth theory of Karl Bucher and Maqashid Syariah. This research is a descriptive qualitative type, with secondary data sources and various literatures to discuss the problem. The results of this study explain that the strategy of the government of Kediri City and Kediri Regency in the economic recovery of the community is included in the Closed Household stage because it is to fulfill the individual needs of the community. In addition, it is also included in the City Household stage because of the potential for economic interaction between regions. When viewed from the Maqashid Syariah, the program run by the government of Kediri City and Kediri Regency has fulfilled five basic principles, such as the maintenance of religion, soul, mind, lineage, and reason.